The effect of season on serum testosterone concentrations in dogs - Mello Martins, Maria Isabel; Souza, Fabiana Ferreira de [UNESP]; Oba, Eunice [UNESP]; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2006)
Photoperiod and environmental temperature are two important factors that may influence the reproductive cycle of various species. The objective of this study was to investigate seasonal influences on serum testosterone concentrations in dogs in a tropical zone, where the variation in day length between winter and summer solstice was approximately 2.5 h. Blood samples were collected every 15 days from seven adult dogs over a 14-month interval and serum testosterone concentrations were determined by radioimmunoassay. The year was divided into four seasons and mean testosterone concentrations for each season were related to the mean environmental temperature and rainfall during that season. Mean testosterone concentrations were 1.81 ng/mL (winter 2002), 1.93 ng/mL (spring 2002),1.31 ng/mL (summer 2003), 2.02 ng/mL (autumn 2003) and 1.93 ng/mL (winter 2003). The temperature ranged from 10.2 to 32.8 degrees C and the rainfall from 33 to 476 mm. Serum testosterone concentrations were lower in summer 2003 than in both spring 2002 (P = 0.05) and autumn 2003 (P = 0.0 16). In a tropical zone, a combination of high temperature and substantial rainfall may have reduced serum testosterone concentrations in dogs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: serum; testosterone; radioimmunoassay; dogs; season